LEGAL CERTAINTY AND ELECTORAL SEPARATION AFTER DECISION 135/PUU-XXII/2024: KEPASTIAN HUKUM DAN PEMISAHAN PEMILU SETELAH PUTUSAN 135/PUU-XXII/2024 - Satmawati; Syamsul Rijal; Muhamad Aksan Akbar (Constitutional Law Society, 2026)
Constitutional Court Decision Number 135/PUU-XXII/2024 has significantly reshaped the discourse on Indonesia’s electoral system by mandating the separation of national and regional elections. While the ruling is presented as a constitutional effort to enhance electoral integrity and administrative effectiveness, it simultaneously raises fundamental concerns regarding legal certainty, particularly in relation to the tenure of members of the Regional People’s Representative Council (DPRD). This study examines the Court’s constitutional reasoning (ratio decidendi) underlying the separation of election schedules and critically assesses its implications for democratic legitimacy and the principle of electoral periodicity. Employing a normative juridical approach that integrates statutory, conceptual, and case-based analysis, this article demonstrates that although the decision may be justified as electoral reform, it risks producing constitutional distortion by blurring the boundary between judicial interpretation and norm creation. Without clear transitional safeguards, the ruling threatens to undermine popular sovereignty and legal certainty in Indonesia’s constitutional framework.